2020
DOI: 10.18406/2316-1817v12n120201414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofertilizer on soil fertility and lettuce nutrition

Abstract: This work aimed to evaluate the effect of the application of efficient microorganisms (EM), in the form of a biofertilizer, on soil fertility and leaf nutrition of lettuce during two crop cycles. One of the biggest challenges of organic production is the fertilization of crops. EMs are considered an alternative, sustainable, safe and low-cost technique to increase the productivity of organic foods, and their use is a good option for agroecological management. For the capture of the EMs and the production of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Lal et al [50] observed that Azotobacter and PSB (phosphate solubilizing bacteria) treatments increased the zinc content in broccoli, and this increase was equivalent to that of chemical fertilizer treatment. In another study, it was reported that biofertilizer-containing microorganisms increased microelements in lettuce plants [51]. According to Altuntaş [38], the B. subtilis strain QST 713 increased the Zn content in broccoli compared to the control.…”
Section: Discussionmentioning
confidence: 95%
“…Lal et al [50] observed that Azotobacter and PSB (phosphate solubilizing bacteria) treatments increased the zinc content in broccoli, and this increase was equivalent to that of chemical fertilizer treatment. In another study, it was reported that biofertilizer-containing microorganisms increased microelements in lettuce plants [51]. According to Altuntaş [38], the B. subtilis strain QST 713 increased the Zn content in broccoli compared to the control.…”
Section: Discussionmentioning
confidence: 95%
“…The impacts of BM inputs on soil quality and crop production have been documented in the literature. The findings highlighted beneficial effects related to BM application, such as (i) increased beneficial soil microorganism abundance and diversity [39]; (ii) improved soil structure [40]; (iii) increased soil nutrient content (e.g., potassium, calcium, and zinc) [41]; (iv) elimination of soilborne pathogens and diseases [42,43]; (v) enhanced plant growth and development [44,45]; and (vi) increased crop yield and quality [46,47]. In addition, certain microbial communities in BM can decompose soil organic matter [48,49].…”
Section: Introductionmentioning
confidence: 96%